Կարինի պատմության մի քանի տվյալների շուրջ (XVIII դ. վերջին քառորդ - XIX դ. առաջին քառորդ) - Մալոյան, Արման
Հոդվածում քննության են առնվել XVIII դարի վերջին և XIX դարի առաջին քառորդների Կարին (Էրզրում) քաղաքի պատմության մի քանի տվյալներ, կատարվել են համապատասխան եզրահանգումներ, ճշգրտումներ ու լրացումներ: XVIII դարի երկրորդ կեսին Արևմտյան Հայաստանի ամենամարդաշատ և ամենահայաշատ քաղաքը Կարին-Էրզրումն էր, և հայոց թիվը XVIII դարի վերջին քառորդին Էրզրումում կազմել է շուրջ 24000-27000 մարդ: Արևմտյան Հայաստանի ամենամարդաշատ քաղաքը լինելուց բացի, Կարինը առևտրի ու արհեստագործության ամենախոշոր կենտրոնն էր: В статье исследованы некоторые факты конца ХVIII века из истории города Карин (Эрзрум), и сделаны определенные выводы, уточнения и дополнения. Во второй половине ХVIII века Карин-Эрзрум был самым густонаселенным городом Западной Армении, где проживало самое большое количество армян. В конце ХVIII века в Карине проживало около 70000-90000 человек. И если, по свидетельству французского путешественника Л.-Ф. Ферьер-Совбефа, одну треть Эрзрума составляли армяне, то в конце ХVIII века их численность составляла около 24000-30000 человек. Будучи самым густонаселенным и самым большим городом с армянским населением Западной Армении, Карин был еще и центром торговли и ремесел. Карин являлся также связующим звеном между торговыми центрами Дамаска, Алеппо, Смирны (Измира), Вана, Диярбакыра, Карса, Токата, Трапезунда, Себастии, Закавказья и Персии. Фактически, в конце ХVIII века и в начале ХIХ века армяне в Карине, не составляя абсолютное большинство, сосредоточили в своих руках торговлю и ремесла в городе. There are some facts of the last 18th century from the history of the city of Karin (Erzrum), and certain conclusions, clarifications and additions in the article. In the second half of the 18th century, Karin-Erzrum was the most populous city in Western Armenia, where the largest number of Armenians lived. At the end of the 18th century about 70,000-90000 people lived in Karin. According to the testimony of the French traveler L.-F. Ferrières-Sauveboeuf, one third of Erzrum were Armenians. At the end of the 18th century the number was about 24,000-30,000 people. Being the most populous and the largest Armenian population city in Western Armenia, Karin was also a center of trade and crafts. Karin was also a link between the shopping centers of Damascus, Aleppo, Smyrna (Izmir), Van, Diyarbakir, Kars, Tokat, Trebizond, Sebastia, Transcaucasia and Persia. In fact, at the end of the 18th century and at the beginning of the 19th century, the Armenians in Karin, not constituting an absolute majority, concentrated trade and crafts in the city in their hands.
Keywords: Հայոց պատմություն